Against the wind creating a church of diversity through authentic love - George, J. Don. (Springfield, Mo. : My Health Church, 2012)
As pastors we have taught our people about God's promise to bless every family on earth through Abraham. We have preached that our mission is to reach the whole world with the gospel. But what about the newcomers from other countries who have moved near our churches? What about those who live under the bridge, people with alternative sexual preferences, and others in our communities? Does the love of God move us to care for them? In this book, Don George shares the story of how God touched his heart and changed the direction of his church. If you want to stick with the status quo, don't bother to read it. But if you sense that God has something more, for you and for your church, open both the book and your heart to an adventure of love, challenge, and the thrill of knowing you're in alignment with God's deepest desires.
Description based on online resource; title from EPUB title page (Library Ideas, viewed May 30, 2013).
Includes bibliographical references.
Keywords: Church attendance; Evangelistic work; Church membership; Pastoral theology; RELIGION / Christian Ministry / Pastoral Resources; RELIGION / Christian Church / Administration; Electronic books